Risk Factors Related to Residential Environment of Childhood Community Acquired Pneumonia - Yeasmin, Shahida; Ara, Chaman; Hossain, Md Belal; Rahman, Fazlur; Bari, Md Washim; Uddin, Md Belal (TAJ: Journal of Teachers Association, 2022)
Introduction: Community-acquired pneumonia (CAP) is a lower respiratory tract infection occurring in a child who has not resided in a hospital or health care facility in the preceding 14 days. This study was done to determine the risk factors related to the residential environment of CAP among children under five. Methods: It was a case-control study conducted at the indoor and outdoor units of the Department of Pediatrics and EPI center of Rajshahi Medical College Hospital (RMCH); the study period was two years, from January 2017 to December 2018. The sampling method was purposive sampling. The sample size was 246 children aged 2-59 months, consisting of 123 cases and 123 controls. Result: A significant association was found between CAP and parental smoking (p =0.000, OR=3.33), overcrowding (p = 0.010, OR =1.96) , indoor air pollution (p = 0.004 ,OR =2.33 ) , exposure to cold & humidity ( p = 0.015 , OR =1.95 ) . The study had identified tobacco smoking of parents, overcrowding, exposure to cold & humidity, indoor air pollution as risk factors for CAP. Conclusion: CAP is an important cause of morbidity and mortality in under five children (2-59 months) in developing countries like Bangladesh. A huge amount of money is needed to treat the CAP. So, it will be a burden on family and country. However, early detection of the significant risk factors and necessary actions toward these factors help us prevent the development of CAP in under five children (2-59 months) and improve their quality of life. TAJ 2022; 35: No-1: 117-123